The Role of Robotics in Enhancing STEM Learning for Young Learners - Samiur Rahman Khan; Nadeem Hossain; Zahid Karim Ullah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
The integration of robotics in education is transforming the way students engage with STEM subjects. This paper explores the effectiveness of robotics in developing problem-solving, programming, and critical thinking skills in young learners. Case studies from various educational institutions demonstrate the positive impact of robotics-based learning in fostering innovation and creativity among children.